Empirical relations for discharge current and momentum injection in dielectric barrier discharge plasma actuators. (31st March 2021) - Tang, Anthony; Vaddi, Ravi Sankar; Mamishev, Alexander; Novosselov, Igor V
Abstract: Dielectric barrier discharge (DBD) plasma actuators with an asymmetric, straight edge electrode configuration generate a wall-bounded jet without moving parts. Mechanistic description of the interaction between the Coulombic forces and fluid motion as a function of DBD parameters remains unclear. This paper presents an experimental investigation of DBD actuators, including electrical current associated with microdischarges, plasma volume and the wall jet momentum over a range of alternating current (AC) frequencies (0.5–2 kHz) and peak-to-peak voltages up to 19.5 kV. Discharge current is measured with a high temporal resolution, plasma volume is characterized optically and the momentum induced by the DBD wall jet is computed based on the axial velocities measured downstream of the actuator using a custom-built pitot tube. Discharge current analysis demonstrated asymmetry between the positive and negative semi-cycle; both currents yielded a power–law relationship with empirical fitting coefficients. Plasma length varies linearly and volume quadratically with voltage. Although plasma length reached an asymptotic value at a higher frequency, the plasma volume grows due to the increasing height of the ionization region. In a simple two-dimensional configuration, the DBD wall jet momentum shows near-linear dependency with discharge current in the range of voltages and frequencies considered in this work. The presented empirical model characterizes the DBD wall jet momentum and the discharge current based only on the AC inputs. With the estimation of plasma volume, the model can be applied for determining more realistic boundary conditions in numerical simulations.